The Momentum Continues: 2026 ASMA Conference Highlights - Marshall Magnusen (Journal of Applied Sports Management, 2026)
The Journal of Applied Sport Management (JASM) is the official publication of the Applied Sport Management Association (ASMA), which is a scholarly organization that builds research partnerships between faculty and students. ASMA also facilitates connections between sport management faculty and students studying sport and practitioners working in the sport industry. In 2026, the annual conference was hosted by Temple University. Highlights from the annual conference include Dr. Robin Hardin from the University of Tennessee receiving the ASMA Distinguished Service and Mentorship Award and Drs. Corr, Petersen, and Stokowski becoming ASMA Research Fellows.
Keywords: management; mentor; service; servant leadership; sport